2016
DOI: 10.1007/s11802-016-2712-7
|View full text |Cite
|
Sign up to set email alerts
|

Composition and distribution of planktonic ciliates in the southern South China Sea during late summer: Comparison between surface and 75 m deep layer

Abstract: Ciliates are very important components in most marine ecosystem. They are trophic link between the microbial food web and grazing food chain. In this study, ciliates were collected from 11 sites in the southern South China Sea (SCS) during August 25 to September 28, 2011. Their composition and distribution at the surface and 75 m deep depth of the ocean were studied. A total of 30 species belonging to 22 genera were identified, and 22 species of 15 genera were Tintinnids. Eutintinnus fraknoii and E. stramentus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been reported that microzooplankton communities were dominated by dinoflagellates and ciliates, and microzooplankton were more abundant in surface waters compared to subsurface waters in the SCS (Yang et al., 2021). Also, the composition of microzooplankton communities was different between surface waters and deeper layers in the SCS (H. Liu et al., 2016; Yang et al., 2021). Dugenne et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that microzooplankton communities were dominated by dinoflagellates and ciliates, and microzooplankton were more abundant in surface waters compared to subsurface waters in the SCS (Yang et al., 2021). Also, the composition of microzooplankton communities was different between surface waters and deeper layers in the SCS (H. Liu et al., 2016; Yang et al., 2021). Dugenne et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that microzooplankton communities were dominated by dinoflagellates and ciliates, and microzooplankton were more abundant in surface waters compared to subsurface waters in the SCS (Yang et al, 2021). Also, the composition of microzooplankton communities was different between surface waters and deeper layers in the SCS (H. Liu et al, 2016;Yang et al, 2021). Dugenne et al (2020) identified potential micro-sized grazers (<200 μm) of UCYN-B in the North Pacific Subtropical Gyre by fitting a Lotka-Volterra model to plankton time series observations, while the potential micro-sized grazers of other UCD taxa are currently unknown.…”
Section: Higher Microzooplankton Grazing Pressure On Ucds In the Lowe...mentioning
confidence: 99%
“…4e). In the southern SCS, 30 and 17 ciliate species were recorded by Liu et al (2016b) and Wu et al (2016c), respectively. Similar to that in the central area, the species richness of tintinnids was distinctively higher than that of aloricated species, in both studies.…”
Section: Oceanic Watermentioning
confidence: 99%
“…Ciliates (phylum Ciliophora) (Lee and Kugrens 1992) have major advantages for such studies due to their easily visible surface patterning and their dramatic and complex behaviors that can be easily analyzed. Moreover, ciliate biomass is a major component of aquatic ecosystems (Lischke et al 2016) because ciliates are effective predators of smaller protists and bacteria, and also serve as an important food source for metazoa, providing a significant link between prokaryotic and eukaryotic food chains (Liu et al 2016, Porter et al 1979).…”
Section: Introductionmentioning
confidence: 99%